Do fluctuations in health expenditure affect economic growth? - James Bukenya (The Open Economics Journal, 2009)
The temporal interdependence between health expenditure and economic growth has been the focus in a number of recent empirical studies. While some insights have been gained from these studies, the focus has been on national economies, either in developed or developing countries. This paper explores this relationship at the U.S. state-level. The paper contributes to the literature by investigating possible dynamic relations between health care expenditure and economic growth, measured by gross state product, in the southeast United States. By employing time series approach, the empirical results confirm the presence of a weak, but positive relationship. After detecting unit roots in the data, cointegration in general, was not detected, as a long-run relationship seemed to exist only for Georgia. The results of the VAR analysis are correspondingly limited. However the shapes of the impulse functions do confirm the proper positive relationship between positive personal health care expenditure changes and economic growth.
Keywords: 330; personal health care expenditure; economic growth; gross state product; time series